2021
DOI: 10.1039/d1lc00618e
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic droplet-based functional materials for cell manipulation

Abstract: Functional materials from the microfluidic-based droplet community are emerging as enabling tools for various applications in tissue engineering and cell biology. The innovative micro- and nano-scale materials with diverse size,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…These controllable multicomponent surface droplets are of great interest in the compartmentalized chemical reactions and microanalytics. 36,76…”
Section: Formation Of Surface Nanodropletsmentioning
confidence: 99%
“…These controllable multicomponent surface droplets are of great interest in the compartmentalized chemical reactions and microanalytics. 36,76…”
Section: Formation Of Surface Nanodropletsmentioning
confidence: 99%
“…Anisotropic hydrogel microparticles, which possess the precise size, shape, and surface texture, have broken through the limitation of general isotropic particles and played a substantial role in many fields, including material science, tissue engineering, and sensing. In particular, as one of the most prominent particle features, engineering surface topography has received increasing attention. Many reports showed that actively changing the surface mesostructure of materials can generate novel biological functions, such as cell adhesion, proliferation, differentiation, and migration. Inspired by this concept, customizing the new surface topography of hydrogel microparticles will provide opportunities for developing novel functions of materials and exploring their new applications in engineering and biology.…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we focus on the most recent developments in microfluidics-assisted formulation of biomaterials, in particular on those with nontrivial internal architecture, typically consisting of multiple distinct compartments. , ,, We use the term “microfluidics” to describe a set of techniques aimed at developing of high-level of control over tiny liquid volumes, typically nano- or even picoliter volumes, at submillimeter length scale. In particular, microfluidics can be used to disperse hydrogel precursor solutions into monodisperse droplets or extrude them into stable jets, which subsequently solidify, either spontaneously or via externally triggered cross-linking reaction, into hydrogel microparticles, ,,,,, microfibers, or more general “microgels”. The laminar (nonturbulent) flow conditions associated with small dimensions of the microchannels lead to reproducibility of droplet and jet morphologies as well as facilitate precise manipulation of the microscopic hydrogel liquid compartments, e.g., their on-chip merging or splitting .…”
Section: Introductionmentioning
confidence: 99%